Knowledge on Hypertension and Self-Care Practice among Adult Hypertensive Patients at University of Gondar Comprehensive Specialized Hospital, Ethiopia, 2019 - Endalkachew, Kidist; Tamene, Firegenet; Ashenafi, Elshaday; Hagos, Desalegn; Asasahegn, Ayele; Worku Kassahun, Chanyalew; Addis, Getachew (International journal of hypertension, 2020)
Background. Patients with hypertension need to be aware of various aspects of hypertension and exercise self-care. But, there is limited information regarding this issue. Objective of the Study. This study was designed to assess knowledge on hypertension and self-care practice among adult hypertensive patients in the University of Gondar Comprehensive Specialized Hospital, Ethiopia. Materials and Methods. Descriptive cross-sectional study was conducted among 384 hypertensive patients from April to May 2019. The study participants were selected using a systematic random sampling technique. Data were collected using a pretested interviewer-administered questionnaire. Descriptive statistics such as percentage and frequency of patients’ knowledge on hypertension and their self-care practice were computed. Cross-tabulation was used to see the frequency and percentage of selected sociodemographic variables and knowledge level with self-care practice subscales. Finally, the results were summarized and presented in texts, figures, and tables. Results. Among the study participants, 215 (56%) and 228 (59.4%) had good knowledge and self-care practice towards hypertension, respectively. The participants who had good knowledge had good self-care practice frequency. Conclusions. In this study, knowledge on hypertension was low, while self-care practice was moderate on the self-care interventions. Hence, increasing patients’ awareness and intervention on medication adherence, low salt diet consumption, physical activity, weight management, cigarette smoking cessation, and alcohol consumption reduction is important.